2017
DOI: 10.1117/12.2264890
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for static charge energy harvesting on aircraft

Abstract: In this paper, the possibility of using the static charge that accumulates on aircraft during flight as a source to power monitoring sensors is examined. The assessed methods include using a pair of materials with different air-flow charging rates, contact discharging of the fuselage to neutral metallic bodies, charge motion induction by the fuselage field and inductive harvesting of fuselage-to-air corona discharges at static discharge wicks. The installation and potential advantages of each method are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A recent review of nanopatterning methods for triboelectric generators can be found in [73]. The implementation of electrodes for inductive exploitation of charge accumulation is a key element in their design [74]. Various implementations have been reported for applications including wearable microsystems [75].…”
Section: The Triboelectric Mechanismmentioning
confidence: 99%
“…A recent review of nanopatterning methods for triboelectric generators can be found in [73]. The implementation of electrodes for inductive exploitation of charge accumulation is a key element in their design [74]. Various implementations have been reported for applications including wearable microsystems [75].…”
Section: The Triboelectric Mechanismmentioning
confidence: 99%
“…In aircraft applications, an alternative EH concept, based on electrostatic charge built up in composite airplane structures during the flight due to the interaction between the airplane and the surrounding atmospheric environment, and its collection with capacitive collectors, a concept at the base of triboelectric (TENG) EH devices as well, was thus investigated in laboratory conditions showing that the electrostatic energy available on the aircraft can be regarded as a DC constant current source [ 109 ]. The subsequent study of the usage of this concept to power monitoring sensors in aircraft confirmed the possibility to collect and store a static charge in a capacitor, but also evidenced the very limited resulting energy outputs of 8 μJ [ 110 ]. The high amount of energy released via static discharging in-flight illustrates, however, the prospective potential of such a technology, also clearly indicating the need for its further investigation.…”
Section: Kinetic Energy Harvesting Systemsmentioning
confidence: 99%
“…Aircraft sensor systems powered by heat [26][27][28][29], vibration [30], flow [31], static charge [32] and by inductive coupling to the electrical power network [33][34][35][36] have been considered. Inductive power transfer methods [37,38] have also been implemented.…”
Section: Introductionmentioning
confidence: 99%